2022
DOI: 10.48022/mbl.2112.12007
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Paulownia tomentosa Fruits in an Experimental Animal Model of Acute Lung Injury

Abstract: The fruits of Paulownia tomentosa (Thunb.) (PT) Steud. have been reported to exert a variety of biological activities. A previous study confirmed that compounds isolated from PT fruits (PTF) exerted anti-inflammatory effects on TNF-α-stimulated airway epithelial cells. However, there is no report on the protective effects of PTF on acute lung injury (ALI). Here, we examined the ameliorative effects of PTF in an experimental animal model of lipopolysaccharide (LPS)-induced ALI. In ALI mice, increased levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The upregulation of various molecules, including cytokines, chemokines, and adhesion molecules, has been reported in the pathogenesis of asthma [ 36 , 51 , 52 ] and in experimental models of inflammatory lung diseases, including AA [ 53 , 54 , 55 ]. Accumulated evidence has indicated that the activation of NF-κB plays a pivotal role in the expression of inflammatory molecules in lung epithelial cells and macrophages [ 5 , 13 , 15 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of various molecules, including cytokines, chemokines, and adhesion molecules, has been reported in the pathogenesis of asthma [ 36 , 51 , 52 ] and in experimental models of inflammatory lung diseases, including AA [ 53 , 54 , 55 ]. Accumulated evidence has indicated that the activation of NF-κB plays a pivotal role in the expression of inflammatory molecules in lung epithelial cells and macrophages [ 5 , 13 , 15 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the MAPK/NF-κB signaling pathways have been admitted as an important target in ALI therapy [26,27], the present study selected these signaling pathways to examine the underlying mechanisms. It was confirmed that FM could suppress the LPS-induced activation of JNK/p38/ERK in in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, mice were administered a mixture of OVA and alum (day 0: 30 µg OVA and 3 mg alum; day 7: 60 µg OVA and 3 mg alum). On days 11-13, mice were administered OVA through inhalation daily for 1 h. On days 9-13, mice were orally administered BGE or dexamethasone (DEX); treatment with 1 mg/kg of DEX is widely used as a positive control for asthma treatment [53][54][55].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…; Bayer Korea, Ltd., Seoul, Republic of Korea) by intraperitoneal injection. On day 15, BALF and serum were collected using a previously reported method [53]. The levels of Th2 cytokines in BALF (R&D systems, Minneapolis, MN, USA) and IgE in serum (Biolegend, San Diego, CA, USA, # 439807) were measured by enzymelinked immunosorbent assay (ELISA) kits, following the manufacturer's instructions.…”
Section: Analysis Of Bronchoalveolar Lavage Fluid (Balf) Of An Animal...mentioning
confidence: 99%